Combination of low-dose glucocorticosteroids and mineralocorticoids as adjunct therapy for adult patients with septic shock: A systematic review and meta-analysis of randomized trials and observational studies - Archontakis Barakakis, Paraschos; Palaiodimos, Leonidas; Fleitas Sosa, Derlis; Benes, Linda; Gulani, Perminder; Fein, Daniel (Avicenna Journal of Medicine, 2019)
Background: The role of the combination of glucocorticosteroids and mineralocorticosteroids in treating septic shock is not well-defined. The aim of this study was to perform a systematic review and meta-analysis of the randomized controlled trials and observational studies assessing the effect of low-dose hydrocortisone and fludrocortisone on patients with septic shock. Materials and Methods: MEDLINE, Scopus, and Cochrane databases were reviewed. A random effect model meta-analysis was used and I-square was used to assess the heterogeneity. Short-term mortality was chosen as our primary end point. A subgroup analysis was performed including only the randomized controlled trials. Results: A total of 10,550 patients were included in this meta-analysis. Administration of the steroid combination was associated with improved short-term mortality (odds ratio, 0.78, confidence interval, 0.64–0.96), intensive care unit mortality, and shock reversal, without increase in steroid-related side effects, such as secondary infection or gastrointestinal hemorrhage. Conclusion: This systematic review and meta-analysis showed that use of the combination of glucocorticosteroids and mineralocorticosteroids has a beneficial impact on short-term mortality, intensive care unit mortality, and shock reversal, without increasing the incidence of gastrointestinal hemorrhage or superinfection in patients with septic shock, when used as an adjunct treatment to the established standard of care.
Keywords: Fludrocortisone; glucocorticosteroids; hydrocortisone; mineralocorticoids; septic shock; steroids